ANALISIS KELAYAKAN NASABAH DALAM PENGAJUAN GADAI BARANG UNTUK USAHA MIKRO KECIL MENENGAH PADA PT. PEGADAIAN CABANG KOLAKA - Putriyanti Putriyanti; Muhammad Akbar (Jurnal Ekonomi Bisnis Syariah, 2020)
In submitting a pledge for goods for this micro and small business, Perum Pegadaian needs to see and analyze the feasibility of a customer, namely by completing the financing application procedure, completing the financing requirements (such as conducting an assessment of prospective customers with 5C aspects (Character, Capacity, Capital, Collateral, Condition), conduct an analysis of the business feasibility of the customer and assess the estimated guarantee held by the customer. The formulation of the problem in this study is how is the feasibility of customers in submitting goods pawns for micro, small and medium enterprises at PT. Pawnshop Kolaka Branch? The aim is to describe the feasibility of customers in submitting pledges for goods for micro and small businesses at PT. Pawnshop Kolaka branch.The approach of this research is a qualitative approach and the type of descriptive research using field data obtained. The data collection instruments used observation sheets, interview sheets, and documentation sheets. The results of the study are aimed at assessing the feasibility of customers used by PT. Pegadaian Kolaka Branch in providing KREASI financing is by completing the financing requirements and fulfilling the KREASI financing procedure. Assessing prospective customers with aspects of 5C (Character, Capacity, Capital, Collateral, Condition), conducting analysis of customer business feasibility and assessing the estimated guarantee owned by customers, namely BPKB for motorbikes or cars. The purpose of the customer's business feasibility assessment is to avoid bad financing where the customer is unable to repay the debt, for this reason a business feasibility analysis is needed in this financing.